Design and optimization of a new compact 2.4 GHz-bandpass filter using DGS technique and U-shaped resonators for WLAN applications - A. Belmajdoub; A. Boutejdar; A. El Alami; S. D. Bennani; M. Jorio (Universitas Ahmad Dahlan, 2019)
The objective of this work is the study, the design and the optimization of an innovative structure of a network of coupled copper metal lines deposited on the upper surface of a R04003 type substrate of height 0.813 with a ground deformed by slots (DGS). This structure is designed in an optimal configuration for use in the design of narrowband bandpass filter for wireless communication systems (WLAN), the aim of use the defected ground structure is to remove the unwanted harmonics in the rejection band, the simulation results obtained from this structure using CST software show a very high selectivity of the designed filter, a very low level of losses (less than-0.45 dB) with a size overall size of 43.5x34.3 mm.